Mathematical Reasoning Ability of Junior High School Students: Application of Discovery Learning Model - Mokoginta, Andika Prasetyo; Hulukati, Evi P.; Kobandaha, Putri Ekawaty (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Mathematical reasoning ability is necessary for solving mathematical problems. Therefore, the intent of this study is to enhance students' mathematical reasoning ability through the application of a discovery learning model focused on quadratic function material. This research is Classroom Action Research, designed by Kemmis and McTaggart. The research subjects were 32 students of grade IX at Public Junior High School 1 Tapa. This study used tests for mathematical reasoning, teacher and student activity observation sheets, and questionnaires. The data was analyzed quantitatively and qualitatively using percentages. The findings of this study indicate an increase in students' mathematical reasoning ability after applying the discovery learning model. Teacher activities in cycle I with a percentage of 73.68% increasing in cycle II to 89.47%; student activities in cycle I with a percentage of 72.50% increasing in cycle II to 87.50%; questionnaire results in cycle I only 20 people with a percentage of 62.50% increasing in cycle II to 28 people with a percentage of 87.50%; and the results of students' reasoning ability in cycle I only 23 people with a percentage of 71.87% increasing in cycle II to 28 people with a percentage of 90.62%. There were still 4 people with a percentage of 9.28% who scored <75. In cycle II, the teacher activities, student activities, questionnaires, and reasoning skills met the success indicators.